Characteristics of Hematology Examination Results and Speed of Recovery of DHF Patients at Bali Mandara Hospital in 2019-2020 - Nugraha, Ketut Yoga Wira; Subawa, Anak Agung Ngurah; Herawati, Sianny; Mulyantari, Ni Kadek (E-Jurnal Medika Udayana; Vol 11 No 10 (2022): E-Jurnal Medika UdayanaDO - 10.24843/MU.2022.V11.i10.P05, 2022)
ABSTRACT Dengue Hemorrhagic Fever (DHF) as one of the most common infectious diseases in the world is still a major concern even though the incidence and mortality rates have decreased. The study objective is to determine hematological examination results and the speed of recovery of DHF patients reviewed according to age, gender, BMI, degree of DHF, and duration of fever before being treated. This was cross-sectional study using secondary data from medical records of 193 DHF patients treated from year 2019 to 2020. In 193 patients, before being admitted to the hospital, the patient had an average fever for 4.12±1.16 days with an average 4.69±1.2 days of hospitalization. Hematological test on hospital admission showed the average platelet value was 83.06±28.74 x10 3 cells/µL with 187 (96.9%) patients had platelet values below the normal value. Average leukocyte count was 4.13±2.01 x 10 3 cells/µL with 126 (65.3%) patients having a leukocyte value below the normal value. Average hematocrit value was 40.31±4.96% with 113 (58.6%) patients had normal hematocrit values. The duration of hospitalization for DHF patients had a significant difference when viewed according to age (p=0.000), BMI (p=0.000), and duration of fever before being treated (p=0.000). The mean platelet values were significantly different when compared according to the duration of fever before being treated (p=0.018). The mean leukocyte values were significantly different when compared according to age (p=0.007) and gender (p=0.008). The mean hematocrit value was significantly different when compared according to age (p=0.000) and gender (p=0.008). Keywords: Dengue hemorrhagic fever, hematological examination, duration of hospitalization